Application of Nutritional, Pharmacological and Physical Therapy Interventions in Delaying Degenerative Changes: Systematic Review - Xue, Wuxin; Awang, Zarina (Journal of Ecohumanism, 2025)
Background: Osteoporosis is a metabolic bone disease that involves mainly those above 50 years of age. Even though pharmacological therapy, which includes bisphosphonates, plays a role in the treatment of osteoporosis, they are basically antiresorptive and are not directly interfering with the overall processes of degeneration seen in senile osteoporosis. Therefore, this limited scope underlines the absolute need for co-treatments that would encompass more aggressively the spectrum of musculoskeletal decline appearing in populations that experience ageing. Aim: The study aimed to investigate the potential of pharmacological, nutritional and physical therapy interventions for delaying degenerative changes in senile osteoporosis. Methodology: This study followed a systematic review. Literatures were identified using inclusion and exclusion criteria, thereby, thirty studies were thematically analysed to derive a findings. Findings: A comprehensive approach that integrates nutritional, pharmacological, and physical therapy interventions shows substantial promise in delaying degenerative changes in senile osteoporosis. Conclusion: Clinicians can apply these insights by creating individualized treatment plans that blend diet, medication, and exercise tailored to patient needs and tolerances. However, the study could be limited by reliance on existing studies due to publication bias. Future studies could aim for randomized controlled trials to assess the lasting effects of such integrated intervention for delaying senile osteoporosis.